Modified method of proportional navigation to intercept aeroballistic targets with a limited sector guidance of missile - V. E. Markevich; V. V. Legkostup (Системный анализ и прикладная информатика)
The improved version of the algorithm realizing a method of proportional navigation for guidance of anti-aircraft guided missiles in the limited sector of the angular tracking connected with the line of sight of the aero ballistic target and the anticipations providing sustainable missile guidance with the maximum the angles of pre-emption, which aren’t exceeding maximum permissible is considered. The analytical expressions describing the algorithm of calculation of guidance command and signals of correction, adaptive to parameters of the movement and realizing steady tracking and control of a guided anti-aircraft missile in the wide the ranges of the radial distance, heights and speeds of the movement of aerodynamic target are given. Results of mathematical simulation of a problem of spatial interception of the aero-ballistic targets and also the comparative analysis and preliminary estimate of accuracy of guidance of the existing classical and modified versions of a method of proportional navigation are presented.